Genome‐wide association study identifies energy metabolism genes for resistance to ketosis in Chinese Holstein cattle. (10th June 2019) - Huang, H.; Cao, J.; Hanif, Q.; Wang, Y.; Yu, Y.; Zhang, S.; Zhang, Y.
Summary: Ketosis (KET) is one common metabolic disorder that occurs mainly in early lactation and affects the dairy industry with significant economic losses. Cows with ketosis have lower milk yield and reproductive performance and greater risk of other periparturient diseases. As a metabolic disease, the pathogenesis of KET is multifactorial. To better understand the genetic background of KET, a genome‐wide association study was performed using the Illumina BovineSNP50 BeadChip. Single‐step genomic BLUP methodology was used to incorporate genomic data into a threshold‐liability model. Results of the GWAS are reported as the proportion of variance explained by 20‐SNP windows. Six genomic regions on Bos taurus autosomes 10, 13, 14 and 25 showed association with KET. Most interestingly, several candidate genes, including previously reported genes ( BMP4, HNF4A and APOBR ) and newly identified genes ( SOCS4, GCH1, ATG14, RGS6, CYP7A1 and MAPK3 ), are involved in insulin metabolism or lipid metabolism, implicating the contribution of energy‐metabolism‐associated genes to the genetic basis of KET. Our results provide new information about the underlying biology and molecular mechanisms associated with KET. Future studies that combine genomic variation analysis and functional gene information may help elucidate the biology of KET.